Big data application prospect of China Tower - Huoming CHENG; Linsu SHI; Shan GAO; Meng JIN; Luda MIAO (Dianxin kexue)
In the past few years,the development of big data technologies has brought new opportunities and challenges in many business sectors.As an important contributor in the telecommunications industry,China Tower has its unique advantages in data.Firstly,the industrial structure of big data was expounded,then the data assets of China Tower were introduced.Finally,the application of big data of China Tower was prospected.